Dialogues of Depth: Exploring Character and Theme in Ana María Rozo's The Little Prince - Efuansyah, Efuansyah (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2024)
Ana María Rozo’s adaptation of The Little Prince delves into the emotional and philosophical depth through dialogue-driven interactions among the Aviator, the Little Prince, and the Fox. While much research has explored the themes of the original story, limited attention has been paid to how dialogue in theatrical adaptations reveals character psychology and advances the narrative. This study addresses that gap by analysing key conversational features such as turn-taking, repair mechanisms, and implicature to uncover how these elements shape character development and thematic exploration. It also investigates how reflective monologues and direct audience engagement enhance the play’s emotional and philosophical resonance. The research focuses on three key questions: (1) How do the dialogues reflect the social and emotional dynamics among characters? (2) What do repair mechanisms and implicatures reveal about character psychology and central themes? (3) How does audience engagement through dialogue amplify the play’s impact? Using an analytical framework centered on conversational dynamics, this study highlights moments such as the Aviator’s isolation being disrupted by the Little Prince’s innocent question,